Assessment of Net Working Capital Management Strategies in the Context of the Covid-19 Pandemic, Using LPP S.A. as an Example - Stawiński, Michał; Soliwoda, Michał (Journal of Finance and Financial Law, 2026)
The purpose of the article. The main objective of the article was to identify the net working capital (NWC) management strategy of LPP S.A. The following research thesis was adopted: LPP S.A., as a trading company, pursued an aggressive NWC strategy from 2019 to 2023. Methodology. Empirical research covered the period from 2019 to 2023 and was performed using economic and financial analysis tools with a focus on ratio analysis. The following companies were used as benchmark companies: VRG S.A., Etos S.A., Wittchen S.A., Wojas S.A., Monnari Trade S.A., CDRL S.A., Esotiq & Henderson S.A., Protektor S.A., VCO S.A. and Hurtimex S.A.. Data was extracted from the EMIS database and LPP S.A.’s financial reports. Critical literature studies were also used in the study. Results of the research. The research confirmed the thesis that LPP S.A. pursued an aggressive working capital management strategy as a commercial enterprise in the years 2019-2023. The aggressive WCM strategy contributed to the company’s higher financial results and was identified on the basis of liquidity, cash cycle, inventory and short-term liabilities ratios, as well as the share of current liabilities and equity in the financing structure.